Improving Optoelectrical Properties of PEDOT: PSS by Organic Additive and Acid Treatment - Shui-Yang Lien; Po-Chen Lin; Wen-Ray Chen; Chuan-Hsi Liu; Po-Wen Sze; Na-Fu Wang; Chien-Jung Huang (Crystals, 2022)
This article demonstrates the change of structural and optical properties of poly (3,4-ethylene dioxythiophene): polystyrene sulfonate (PEDOT: PSS) by organic additive and acid treatment. The addition of sorbitol and maltitol can disperse the micelles of PEDOT: PSS. The mechanism of the bond-breaking reaction was investigated and a model for the bond-breaking reaction is also proposed. Furthermore, multiple formic acid treatments were found to reduce the PSS content of PEDOT: PSS, resulting in an enhancement in conductivity (4.2 × 104 S/m).